The effect of the family empowerment model on the ability to managing diet and increasing hemoglobin in pregnant women - Kasad Kasad; Keumalahayati Keumalahayati; Azwarni Azwarni; Meliani Sukmadewi Harahap; Alfian Helmi (AcTion: Aceh Nutrition Journal, 2023)
Anemia often occurs due to iron deficiency because, in pregnant women, there is a doubling of an iron requirement to meet the mother's needs in preventing blood loss during childbirth and fetal growth. Therefore, anemia in pregnant women must be prevented so that the fetus can grow and develop properly. This study aimed to determine the effect of the family empowerment model on the ability to manage diet and increase hemoglobin (Hb) levels in pregnant women with anemia. The research design was quasi-experimental, conducted at the Langsa Baro Health Center work area in 2018. The sample comprised 30 pregnant women divided into two groups, namely 15 women who received intervention and 15 who did not. Sampling was performed using the purposive sampling technique, and data were collected through direct interview techniques with questionnaire instruments. Data processing was performed by statistical analysis using a Paired T-test test with a significance level of 95% CI. The results showed differences in Hb levels, knowledge, and attitudes before and after family empowerment (p <0,05). In conclusion, there was a significant effect on the ability to manage diet and increase hemoglobin (Hb) levels in pregnant women with anemia.